Subarachnoid hemorrhage: New insights on pathogenesis - Nwafor, Divine C.; Brichacek, Allison L.; Rallo, Michael S.; Bidwai, Nina; Marsh, Robert A. (Frontiers in Stroke, 2023)
Subarachnoid hemorrhage (SAH) is a type of hemorrhagic stroke characterized by high morbidity and mortality. Saccular intracranial aneurysms account for most cases of SAH. While the role of hemodynamic stress and inflammation have been extensively studied in SAH, little is known about the role of the microbiome in SAH despite recent studies uncovering new insights on the effects of microbiome alteration in ischemic stroke. This review presents the current knowledge around the role of the microbiome in intracranial aneurysm formation and rupture. We also highlight the influence of diet on intracranial aneurysm formation and provide evidence that corroborates the targeting of inflammatory pathways as a potential strategy to curb SAH-associated neurological dysfunction.